Governor-General N. G. Kaznakov on most important issues of governance in Western Siberia - V. V. Germizeeva (Омский научный вестник: Серия "Общество. История. Современность")
The article analyzes the content of records management documents related to the performance of the activities of the Governor-General of Western Siberia N. G. Kaznakov. Attention is drawn to the problems in the management of the region, which are reflected in the documents and possible ways to solve them. First of all, these are issues of education, medicine, the state of veterinary, the position of foreigners, the development of means of communication and much more. The author notes that representatives of the central government, as a rule, were attentive to the proposals of N. G. Kaznakov, who were supposed to promote the gradual unification of life at that time of the remote region with the European part of Russia